(untitled) (Research, Society and Development, 2023)
Introduction: In Brazil, there is an accelerated aging of the population, which is more susceptible to falls and, as a consequence, femur fractures. In this sense, this trauma is one of the main public health problems, due to the complications and sequelae, in addition to requiring a long recovery period, showing a huge implication in public health, being associated with high financial expenditure. Objective: To analyze the socioeconomic impact and epidemiological profile of hospitalizations of elderly people due to femur fractures in the public health system in Ananindeua, Pará. Methods: This was a retrospective, descriptive observational study using data from the SUS Hospital Information System. Results: Femur fractures in the municipality of Ananindeua, Pará, totaled 610 hospitalizations, especially in 2020, and the epidemiological profile was demarcated by females, brown people, aged 80 or over. In addition, the average length of hospital stay and mortality were directly associated. Conclusion: Although there are an adequate number of studies on the subject, there is still a need for more up-to-date studies, especially on measures for prophylaxis and faster treatment for the correction of these fractures.